Biodiesel production from palm oil and methanol via zeolite derived catalyst as a phase boundary catalyst: An optimization study by using response surface methodology - Zhang, Pingbo; Chen, Xuan; Leng, Yan; Dong, Yuming; Jiang, Pingping; Fan, Mingming (Fuel (Guildford), 2020)
[Display omitted] •Lithium-modified mesoporous zeolite as a phase boundary catalyst for biodiesel production.•Monodisperse of catalyst in methanol promote the formation of CH3O–.•The excellent reuse performance and regeneration performance of zeolite catalyst.•The highest biodiesel yield reached 99.68% by Response Surface Methodology. A zeolite derived catalyst was prepared by lithium modified zeolites, which can be used as a phase boundary catalyst for the reaction of soybean oil or palm oil with short chain alcohols such as methanol or ethanol. The zeolite derived catalyst was characterized by XRD, TG, SEM, CO2-TPD, DLS and contact angles (CA). The results showed that Li3AlSiO5, the main active components of the zeolite derived catalyst, had excellent catalytic activity. The surface of the zeolite derived catalyst possess the complex pore structure, and zeolite derived catalyst belonged to monodisperse system in methanol suspension. Small molecules such as methanol could diffuse easily, and fully contacted the active sites on the surface of zeolite derived catalyst, which would promote the formation of CH3O–. Interestingly, the optical contact angle indicated that the zeolite derived catalyst had a strong hydrophilicity, so that the zeolite derived catalyst was located between the two-phase boundary of the alcohol and oil. It would offer large interfacial area and overcome the mass transfer obstacles between the multi-phase, effectively enhanced the reaction rate. Furthermore, the stability test confirmed that the zeolite derived catalyst had good reusability and universality. The Response Surface Methodology (RSM) was used to optimize the process parameters of palm oil and methanol in the synthesis of biodiesel, which has better guiding significance for the industrial production of biodiesel in the future.